Effect of homogenization rates on the properties and stability of fish gelatin films with cinnamon essential oil - Lee, See Cheng; Foong, Han Lyn; Zainal Abedin, Nur Hanani (Tech Science Press, 2025)
Fish gelatin films have emerged as eco-friendly packaging materials due to their biodegradability and excellent film-forming properties. This study investigated the effects of varying homogenization rates (0, 6500, 9500, 13,500, 17,500, and 21,500 rpm) on the functional and structural properties of fish gelatin films enriched with cinnamon essential oil (CEO). Homogenization reduced droplet sizes and narrowed droplet size distributions in the film-forming emulsion (FFE). At a homogenization rate of 9500 rpm, the films exhibited excellent mechanical extensibility, reduced surface irregularities, and enhanced smoothness. The highest (p < 0.05) tensile strength and elongation at break were observed at this rate, showing increases of 57% and 14%, respectively, compared to the control film made from non-homogenized FFE. However, further increases in homogenization rates significantly increased (p < 0.05) water vapor permeability and caused CEO droplets aggregation, leading to increased surface irregularities and the formation of pores in the film microstructure. These structural changes were observed through confocal laser scanning microscopy (CLSM), scanning electron microscopy (SEM), and atomic force microscopy (AFM). These findings indicate that the film properties were significantly influenced by the homogenization rate, highlighting its role in tailoring the mechanical and barrier properties of fish gelatin/CEO films for food packaging applications.